2015
DOI: 10.18632/oncotarget.6276
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent high-dose treatment with erlotinib enhances therapeutic efficacy in EGFR-mutant lung cancer

Abstract: Treatment with EGFR kinase inhibitors improves progression-free survival of patients with EGFR-mutant lung cancer. However, all patients with initial response will eventually acquire resistance and die from tumor recurrence. We found that intermittent high-dose treatment with erlotinib induced apoptosis more potently and improved tumor shrinkage significantly than the established low doses. In mice carrying EGFR-mutant xenografts intermittent high-dose treatment (200 mg/kg every other day) was tolerable and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 35 publications
2
28
0
1
Order By: Relevance
“…However, some studies showed Gefitinib has no benefit to chemotherapy , possibly due to incomplete inhibition of the EGFR tyrosine kinase with daily Gefitinib therapy and/or the development of resistance to chemotherapy [ 23 , 24 ]. Intermittent high-dose EGFR has shown the potential to overcome these theoretical limitations of daily dosing in several studies [ 14 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies showed Gefitinib has no benefit to chemotherapy , possibly due to incomplete inhibition of the EGFR tyrosine kinase with daily Gefitinib therapy and/or the development of resistance to chemotherapy [ 23 , 24 ]. Intermittent high-dose EGFR has shown the potential to overcome these theoretical limitations of daily dosing in several studies [ 14 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, 1.0×10 6 exponentially growing cells with ectopic expression of appropriate genes were injected subcutaneously. Tumor volume was estimated using calipers every week ((length* width^2)/2) [ 44 ], then in the sixth week after injection, animals were sacrificed. Tumor nodules were harvested and measured, then immunohistochemically stained with PCNA to assess the proliferation of cells.…”
Section: Methodsmentioning
confidence: 99%
“…Schedules and dosing represent a blend of the maximally effective dose and/or maximally tolerated dose based on several experiments conducted by Charles River Discovery. Doses are in a range that reflects preclinical studies that have been seen previously in the literature [ 25 33 ].…”
Section: Resultsmentioning
confidence: 99%